An Automated Computer‐Vision "Bubble‐Counting" Technique to Characterise CO2 Dissolution into an Acetonitrile Flow Stream in a Teflon AF‐2400 Tube‐in‐Tube Flow Device. Issue 1 (23rd August 2022) - O'Brien, Matthew; Moraru, Ruxandra
Abstract: A Teflon AF‐2400 based tube‐in‐tube device was used to generate flow streams of CO2 in acetonitrile and a computer‐vision based 'bubble counting' technique was used to estimate the amount of CO2 that had passed into solution whilst in the tube‐in‐tube device by quantifying the amount of CO2 that left solution (forming separate gas‐phase segments) downstream of the back‐pressure regulator. For both CO2 pressures used, there appeared to be a minimum residence time below which no CO2 was observed to leave solution. This was assumed to be due to residual CO2 below (or close to) the saturation concentration at atmospheric pressure and, by taking this into account, we were able to fit curves corresponding to simple gradient‐driven diffusion and which closely matched previously obtained colorimetric titration data for the same system. The estimated value for the residual concentration of CO2 (0.37 M) is higher than, but in reasonable general correspondence with, saturation concentrations previously reported for CO2 in acetonitrile (0.27 M). Abstract : A computer‐vision 'bubble counting' approach was used to estimate CO2 dissolution into acetonitrile in a Teflon AF‐2400 tube‐in‐tube device. The observed differences to our previously reported methodology (inline titration) can be accounted for if residual dissolved CO2 (that doesn't outgas) is taken into consideration.